Synchronization of Intracellular Ca2+ Release in Multicellular Cardiac Preparations - Slabaugh, Jessica L.; Brunello, Lucia; Elnakish, Mohammad T.; Milani-Nejad, Nima; Gyorke, Sandor; Janssen, Paul M. L. (Frontiers in Physiology, 2018)
In myocardial tissue Ca2+ release from the sarcoplasmic reticulum (SR) occurs via the ryanodine receptor (RyR2) channel complex. Ca2+ release through RyR2 can be either stimulated by an action potential (AP) or spontaneous. The latter is often associated with triggered afterdepolarizations, which in turn may lead to sustained arrhythmias. It is believed that some synchronization mechanism exists for afterdepolarizations and action potentials (APs) in neighboring myocytes, possibly a similarly timed recovery of RyR2 from refractoriness, which enables RyR2s to reach the threshold for spontaneous Ca2+ release simultaneously. To investigate this synchronization mechanism in absence of genetic factors that predispose arrhythmia, we examined the generation of triggered activity in multicellular cardiac preparations. In myocardial trabeculae from the rat, we demonstrated that in the presence of both isoproterenol and caffeine, neighboring myocytes within the cardiac trabeculae were able to synchronize their diastolic spontaneous SR Ca2+ release. Using confocal Ca2+ imaging, we could visualize Ca2+ waves in the multicellular preparation; while these waves were not always present in every myocyte within the trabeculae, we observed that, over time, the Ca2+ waves can synchronize in multiple myocytes. This synchronized activity was sufficiently strong that it could trigger a synchronized, propagated contraction in the whole trabecula encompassing even previously quiescent myocytes. The detection of Ca2+ dynamics in individual myocytes in their in situ setting at the multicellular level exposed a synchronization mechanism that could induce local triggered activity in the heart in the absence of global Ca2+ dysregulation.